Case Report: Catatonia Associated With Post-traumatic Stress Disorder - Ahmed, Gellan K.; Elbeh, Khaled; Karim, Ahmed A.; Khedr, Eman M. (Frontiers in Psychiatry, 2021)
We report here about a 12 years-old, female patient who had two life threatening accidents that lead to post traumatic stress disorder associated with catatonia. She had closed eyes, urinary and fecal incontinence, and had been in an abnormal position for one and half month. Moreover, she had complications with dehydration, mutism, malunion of the fractured arm and deformities in hand and foot. After detailed psychiatric examination, neurological assessment and laboratory investigation the patient received successful treatment in the form of benzodiazepine injection, intravenous fluid, oral antidepressant and six sessions of Electroconvulsive therapy (ECT). To our knowledge, this is the first case report for catatonia associated post-traumatic stress disorder in a child who did not have resignation syndrome. We discuss the pathophysiology of catatonia, which remains elusive, and recommend evaluating catatonic children for any possible trauma during psychiatry assessment.